Petr Drulák, Šárka Moravcová (eds.): Non-Western Reflection on Politics - Alfred Kramar (Czech Journal of International Relations, 2016)
Petr Drulák – Šárka Moravcová (eds.): Non-Western Reflection on Politics. 1. vydání. Frankfurt nad Mohanem: Peter Lang GmbH, 2013, 259 stran, ISBN 978-3-631-64354-9 (signatura knihovny ÚMV 59 835).